The covid-19 impact on exports in North Macedonia—firm-level analysis. Issue 1 (9th April 2022) - Srbinoski, Bojan; Petreski, Blagica; Petreski, Marjan
Abstract: Exports experienced extraordinary growth rates during the last decade in North Macedonia capturing above 50% share of the country's GDP. However, the COVID-19 crisis interrupted the positive export series imposing various constraints in multiple dimensions on export-oriented firms. This study explores the multidimensionality of the COVID-19 impact on exporters in North Macedonia. We find that COVID-19 caused a systematic slowdown in the exporters' revenue, profit, investment, capital, employment and salaries growth rates. Moreover, the limited access to finance, import exposure to EU markets, high labour-intensity, export exposure to non-EU markets and lower competitiveness make exporters less resilient to the pandemic shocks representing the main obstacles exporters are/will be facing in the recovery stage.